Inclusion of a Notary Public Protection Clause in the Deed of Parties, Legalization, Waarmerking, Adjustment and Matching of Copies with the Original and Kovernot - Habib Adjie (Budapest International Research and Critics University, 2021)
When a Notary violates this article while doing his or her job duties, it qualifies as an act without authority. As a consequence of such an act without authority, someone who is harmed by a Notary who has declared his position without authority can sue for civil damages and compensation to the Notary Public. In carrying out these responsibilities, the notary is protected by the Notary Position Law (UUJN) and the UUJN-P. However, other forms of protection can be carried out and developed by the notary himself, namely by including the Self-Protection Clause in the deed made before the Notary Public. or when at the request of the parties making Legalization, Waarmerking, Adjustment / Matching of the Copy with the Original and Kovernot. Such a Notary Self-protection is very important for the notary so that no one quickly questions the notary's deed of Legalization, Waarmerking, Adjustment / Matching of Copies with the Original and Kovernot. So the notary is obliged to protect himself.